Plasmacytoid dendritic cells drive acute asthma exacerbations - Chairakaki, Aikaterini-Dimitra; Saridaki, Maria-Ioanna; Pyrillou, Katerina; Mouratis, Marios-Angelos; Koltsida, Ourania; Walton, Ross P.; Bartlett, Nathan W.; Stavropoulos, Athanasios; Boon, Louis; Rovina, Nikoletta; Papadopoulos, Nikolaos G.; Johnston, Sebastian L.; et al. (Journal of allergy and clinical immunology, 2018)
Although acute exacerbations, mostly triggered by viruses, account for the majority of hospitalizations in asthmatic patients, there is still very little known about the pathophysiologic mechanisms involved. Plasmacytoid dendritic cells (pDCs), prominent cells of antiviral immunity, exhibit proinflammatory or tolerogenic functions depending on the context, yet their involvement in asthma exacerbations remains unexplored. We sought to investigate the role of pDCs in allergic airway inflammation and acute asthma exacerbations. Animal models of allergic airway disease (AAD) and virus-induced AAD exacerbations were used to dissect pDC function in vivo and unwind the potential mechanisms involved. Sputum from asthmatic patients with stable disease or acute exacerbations was further studied to determine the presence of pDCs and correlation with inflammation. pDCs were key mediators of the immunoinflammatory cascade that drives asthma exacerbations. In animal models of AAD and rhinovirus-induced AAD exacerbations, pDCs were recruited to the lung during inflammation and migrated to the draining lymph nodes to boost TH2-mediated effector responses. Accordingly, pDC depletion after allergen challenge or during rhinovirus infection abrogated exacerbation of inflammation and disease. Central to this process was IL-25, which was induced by allergen challenge or rhinovirus infection and conditioned pDCs for proinflammatory function. Consistently, in asthmatic patients pDC numbers were markedly increased during exacerbations and correlated with the severity of inflammation and the risk for asthma attacks. Our studies uncover a previously unsuspected role of pDCs in asthma exacerbations with potential diagnostic and prognostic implications. They also propose the therapeutic targeting of pDCs and IL-25 for the treatment of acute asthma. [Display omitted]